Human dermal fibroblast-derived exosomes induce macrophage activation in systemic sclerosis. (10th August 2022) - Bhandari, Rajan; Yang, Heetaek; Kosarek, Noelle N; Smith, Avi E; Garlick, Jonathan A; Hinchcliff, Monique; Whitfield, Michael L; Pioli, Patricia A
Abstract: Objectives: Prior work demonstrates that co-cultured macrophages and fibroblasts from patients with SSc engage in reciprocal activation. However, the mechanism by which these cell types communicate and contribute to fibrosis and inflammation in SSc is unknown. Methods: Fibroblasts were isolated from skin biopsies obtained from 7 SSc patients or 6 healthy age and gender-matched control subjects following written informed consent. Human donor-derived macrophages were cultured with exosomes isolated from control or SSc fibroblasts for an additional 48 h. Macrophages were immunophenotyped using flow cytometry, qRT-PCR and multiplex. For mutual activation studies, exosome-activated macrophages were co-cultured with SSc or healthy fibroblasts using Transwells. Results: Macrophages activated with dermal fibroblast-derived exosomes from SSc patients upregulated surface expression of CD163, CD206, MHC Class II and CD16 and secreted increased levels of IL-6, IL-10, IL-12p40 and TNF compared with macrophages incubated with healthy control fibroblasts ( n  = 7, P  < 0.05). Exosome-stimulated macrophages and SSc fibroblasts engaged in reciprocal activation, as production of collagen and fibronectin was significantly increased in SSc fibroblasts receiving signals from SSc exosome-stimulated macrophages ( n  = 7, P  < 0.05). Conclusion: In this work, we demonstrate for the first time that human SSc dermal fibroblasts mediate macrophage activation through exosomes. Our findings suggest that macrophages and fibroblasts engage in cross-talk in SSc skin, resulting in mutual activation, inflammation, and extracellular matrix (ECM) deposition. Collectively, these studies implicate macrophages and fibroblasts as cooperative mediators of fibrosis in SSc and suggest therapeutic targeting of both cell types may provide maximal benefit in ameliorating disease in SSc patients.